2011
DOI: 10.1021/ci1004527
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Virtual High-Throughput Screening Methods for the Identification of Phosphodiesterase-5 Inhibitors

Abstract: Reliable and effective virtual high-throughput screening (vHTS) methods are desperately needed to minimize the expenses involved in drug discovery projects. Here, we present an improvement to the negative image-based (NIB) screening: the shape, the electrostatics, and the solvation state of the target protein's ligand-binding site are included into the vHTS. Additionally, the initial vHTS results are postprocessed with molecular mechanics/generalized Born surface area (MMGBSA) calculations to estimate the favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 47 publications
2
54
0
Order By: Relevance
“…Although many computer-aided drug discovery methods treat ligands flexibly, a rigid protein structure is used to limit computational cost. Utilization of multiple crystal structures has been applied as a valid method for simulating protein flexibility [19][20][21][22]. In this work, we tested the usage of two rigid crystal structures in each target protein to imitate the flexibility of the protein structure without the need to use computationally laborious methods such as molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many computer-aided drug discovery methods treat ligands flexibly, a rigid protein structure is used to limit computational cost. Utilization of multiple crystal structures has been applied as a valid method for simulating protein flexibility [19][20][21][22]. In this work, we tested the usage of two rigid crystal structures in each target protein to imitate the flexibility of the protein structure without the need to use computationally laborious methods such as molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we tested the usage of two rigid crystal structures in each target protein to imitate the flexibility of the protein structure without the need to use computationally laborious methods such as molecular dynamics simulations. Our previous study [22] tested the usage of computationally demanding combination of molecular dynamics simulations and binding free energy calculations with molecular mechanics Poisson-Boltzmann/generalized born area (MMPB/GBSA [23,24]). Even though our method emphasizes speed, we do not want to sacrifice the ability to reproduce reasonable binding poses because successful virtual screening caused by wrong reasons or by accident is not sustainable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, drug discovery processes such as virtual screening can be assisted by the free energy calculations with small molecules (Niinivehmas et al 2011). Other examples of applications that can be advanced with the help of Gbind estimations include ranking both small-molecule (Hou et al 2011) and peptide ligands (Zuo et al 2012) on the grounds of their binding affinity.…”
Section: Mm-gbsamentioning
confidence: 99%
“…In computational simulations with an applied external force, the unmasking has been observed for domain pairs FLNa18-19 andFLNa20-21 (Pentikäinen &Ylänne 2009, Chen et al 2009). However, it has also been suggested that mechanical stretch is not necessarily a requisite for the release of the auto-inhibition (Ithychanda & Qin 2011, Pentikäinen et al 2011. It seems that excess ligand peptides, at least in the case of migfilin and filamin, may compete with the masking and release the autoinhibition.…”
mentioning
confidence: 99%